Clinical and Hematological Parameters as the Predictors of Shock in Dengue Infection - Utami Mulyaningrum; Khairunisa Wardani (Universitas Islam Bandung, 2018)
Dengue infection is one of the main health issues in the world and Asia has the highest incidence of dengue infection with most children aged 5–15 years affected. As World Health Organization (WHO) guidelines recommend, the identification of warning signs at defervescence can detect patients who are at risk of progression to shock. This study aimed to determine the clinical and hematological parameters as the predictors of shock in dengue infection. This retrospective study collected medical records of pediatric patients suffering from dengue infection admitted to dr. Soediran Mangun Sumarso Regional Hospital in Wonogiri, Central Java in January–November 2016. Data was collected in December 2016. The studied predictor factors consisted of clinical and hematological parameters that represented the warning signs of dengue infection. Statistical analysis was performed using the logistic regression test. Of the 110 eligible subjects, 33 (30%) of them suffered from dengue shock syndrome. The multivariate analysis showed that gastrointestinal bleeding (OR=32.62), pleural effusion (OR=31.45), hematocrit >45% (OR=8.67), and thrombocytopenia ≤50,000/µL (OR=13) increased the risk of dengue shock syndrome. Clinical parameters as gastrointestinal bleeding and pleural effusion as well as laboratory parameters of hematocrit and thrombocytopenia became the predictors of shock in dengue infection. PARAMETER KLINIS DAN HEMATOLOGIS SEBAGAI PREDIKTOR KEJADIAN SYOK PADA INFEKSI DENGUEInfeksi dengue merupakan salah satu masalah kesehatan utama di dunia. Asiamerupakan kawasan dengan insidensi infeksi dengue tertinggi dengan penderita terbanyak anak berusia 5–15 tahun. World Health Organization (WHO) menyatakan bahwa tanda bahaya dengue pada fase kritis dapat mendeteksi kejadian syok pada pasien. Tujuan penelitian ini adalah menentukan parameter klinis dan hematologis yang menjadi prediktor syok pada infeksi dengue. Penelitian ini merupakan penelitian retrospektif dengan mengumpulkan data rekam medis pasien anak yang menderita infeksi dengue dan dirawat di RSUD dr. Soediran Mangun Sumarso Wonogiri Jawa Tengah pada Januari–November 2016. Pengambilan data dilakukan pada bulan Desember 2016. Faktor prediktor yang diteliti adalah parameter klinis dan hematologis yang merupakan tanda bahaya infeksi dengue. Analisis statistik dilakukan menggunakan uji regresi logistik. Dari 110 subjek penelitian yang memenuhi kriteria, 33 (30%) di antaranya menderita sindrom syok dengue. Analisis multivariat menunjukkan perdarahan saluran cerna (OR=32,62), efusi pleura (OR=31,45), hematokrit >45% (OR=8,67), dan jumlah trombosit ≤50.000/µL (OR=13) meningkatkan risiko sindrom syok dengue. Parameter klinis berupa perdarahan saluran cerna dan efusi pleura serta parameter laboratoris berupa hematokrit dan jumlah trombositopenia merupakan prediktor kejadian syok pada infeksi dengue.